Microwave breast imaging for cancer diagnosis: An overview - Felício, J. M.; Martins, R. A.; Costa, J. R.; Fernandes, C. A. (IEEE Antennas and Propagation Magazine, 2024)
Microwave (MW) breast imaging has been investigated as a complementary breast diagnosis modality for more than 30 years, and it is still an active field of research. We discuss the challenges concerning antenna design and provide a “lookup tool” to help researchers with the selection of the best antenna to suit their needs. Moreover, we examine the algorithms proposed for radar and tomography imaging systems and review how machine learning (ML) techniques have been applied to MW signals to detect signatures or patterns that are otherwise impossible to detect. We discuss data fusion techniques that merge MW and other technologies or signal processing techniques. Finally, we identify open challenges on software and hardware components so that MW breast imaging (MWBI) may become an effective primary diagnosis modality.